Kontrol dan Monitoring Absensi dengan menggunakan mesin absensi Finger Print: Studi kasus di PT Greenindo Plastiktama (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This project aims to design and implement a manual attendance system as an alternative solution for PT Greenindo Plastiktama Industri. The system addresses issues with the fingerprint attendance system, particularly during system errors or for part-time employees. Methods employed in this study include interviews, observations, and documentation to thoroughly understand the partner's needs. The implementation results indicate that the manual attendance system assists the HR department in recording attendance efficiently and provides an easily accessible alternative for employees. The conclusion of this study highlights that the manual attendance system, designed to be simple, flexible, and tailored to the company’s needs, effectively enhances attendance recording efficiency and supports overall company operations.